Hildebrand solubility parameters of ionic liquids : effects of ionic liquid type, temperature and DMA fraction in ionic liquid - Weerachanchai, Piyarat (2013)
The Hildebrand solubility parameters of 10 ionic liquids were investigated using the approach of intrinsic viscosity. Effects of dimethylacetamide (DMA) fraction in ionic liquids and dissolution temperature on the Hildebrand solubility parameter were also studied. Moreover, cohesive energy density, molar internal energy and enthalpy of dissolution were calculated. Cation and anion of an ionic liquid shows a significant influence on the solubility parameter. The values of ionic liquids containing BMIM cations are in the following order: [PF6] > [Tf2N] > [Cl], while those of ionic liquids containing EMIM cations are in the order: [BF4] > [DEPO4] > [AC]. Ionic liquid containing HOEMIM exerts the highest solubility parameter than that containing MBPYRRO or BMIM. Considering effect of varying DMA fraction, the Hildebrand solubility parameters of the mixtures do not correspond to the mixing rule. Their values tend to be closer to those of the ionic liquids than that of DMA for 40–90 vol% DMA added in the ionic liquids (1-Ethyl-3-methylimidazolium acetate (EMIM-AC) and 1-Butyl-3-methylimidazolium chloride (BMIM-Cl)). With increasing temperature from 25 to 60 °C, decreases of Hildebrand solubility parameters from 25.2 to 24.7 for EMIM-AC and the mixture of EMIM-AC/DMA (60–40 v/v) were obtained. The cohesive energy densities of ionic liquids at the different conditions are proportional directly with the Hildebrand solubility parameter. The molar internal energy and the enthalpy of dissolution decrease with increasing DMA fraction in ionic liquids, while they are almost constant or show slight decreases with the increase of dissolution temperature for EMIM-AC and the mixture of EMIM-AC/DMA (60–40 v/v), respectively.